Tungsten Nitride‐Cobalt Anchored in N‐Doped Ordered Porous Carbon as an Efficient Oxygen Reduction Reaction Electrocatalyst. Issue 1 (30th November 2016) - Zhou, Yan; Xue, Hairong; Wang, Tao; Guo, Hu; Fan, Xiaoli; Song, Li; Xia, Wei; Gong, Hao; He, Yuping; Wang, Junwei; He, Jianping
Abstract: We prepared a non‐precious‐metal tungsten nitride‐cobalt (WN‐Co) electrocatalyst anchored in nitrogen‐doped ordered porous carbon (NOPC) through an in situ method. The WN‐Co/NOPC electrocatalyst possesses good oxygen reduction reaction (ORR) capability in alkaline media, including a high onset potential of −132 mV, a dominant four‐electron process, and a superior stability (onset potential and limiting current density were almost unchanged after 5000 cycles in 0.1 m KOH). The improved ORR performance was comparable to that of WN/NOPC and Co/NOPC with regard to three aspects: the even dispersion and uniform size of electrocatalyst particles provide more reactive sites; the nitrogen doping, high specific surface area and highly ordered mesoporous channel of catalyst support (NOPC) are conducive to the infiltration of the electrolyte; the existence of WN reinvests the catalyst with good stability, and the anchored configuration of WN and Co in the NOPC will prevent the particles from agglomerating after a long‐term cycle, thereby improving the stability of the catalyst particles. Abstract : Cheap as chips : The non‐precious‐metal tungsten nitride‐cobalt/nitrogen‐doped ordered porous carbon (WN‐Co/NOPC) has been developed through a facile in situ synthesis. It exhibits an excellent activity and stability because of its ordered porous structure, nitrogen doping, high dispersion of WN‐Co nanoparticles and the ensemble effects between the WN and Co phases, making it a promising cathode catalyst in fuel cells.